Combinatorial and Additive Number Theory CANT 2011 and 2012 - Nathanson, Melvyn B. (Springer Proceedings in Mathematics & Statistics, 2014)
This proceedings volume is based on papers presented at the Workshops on Combinatorial and Additive Number Theory (CANT), which were held at the Graduate Center of the City University of New York in 2011 and 2012. The goal of the workshops is to survey recent progress in combinatorial number theory and related parts of mathematics. The workshop attracts researchers and students who discuss the state-of-the-art, open problems, and future challenges in number theory.